'. . . staff here are just dropped in the deep end': The Impact of Roles on Communication and Supervisor Support in Youth Custody. (September 2022) - Paterson-Young, Claire
Staff experience in youth custody are often categorised by strains, which are affected by communication and support. This research explores the association between staff roles, within a Secure Training Centre in the England, and the levels of communication and support. It enhances our understanding of the challenges faced by staff members working with young people in custodial settings and how levels of communication and support are dictated by staff roles. Through questionnaires ( N = 74) and interviews ( N = 15) with staff, statistically significant relationship between staff role and levels of communication and support was identified. Through triangulation, this article illustrates the effectiveness of the job demands–resources model in understanding staff experiences with communication and supervisory support in youth custody. It has wide-ranging implications by providing sociologists with an effective model for understanding job satisfaction and stress and by providing policy-makers and organisations delivering custodial services an understanding of the communication and support required to reduce stress and turnover.